Performance of the Recycled and Copper-Doped Materials from Spent Electrodes by XPS and Voltammetric Characteristics. Issue 9 (8th June 2020) - Rada, S.; Unguresan, M.; Rada, M.; Tudoran, C.; Wang, Jiaou; Culea, E.
Abstract : Recycling of electrodes from a car battery and doping them with high CuO content was achieved by the melt quenching method. As sources of PbO2 and Pb, the active mass of the anode (Pb) and the cathode (PbO2 ) of a spent lead accumulator was used. The analysis of X-ray diffractograms shows that by the doping the recycled electrodes from the spent car battery with high CuO content there is an increasing conversion of the metallic plate made mainly of metallic lead in vitroceramic containing PbO2 and nanoparticles of Cu2 O. UV–vis data indicate the presence of Pb +2, Cu +1 and Cu +2 ions in the structure of the electrodes. Values of the optical band gap energies are smaller than 3 eV indicating a semiconductor behavior of the samples. EPR data indicate resonance lines provided from contributions of the isolated Cu +2 ions overlap with the broader resonance lines corresponding to the clustered and/or coupled Cu +2 ions. Cyclic voltamograms of the electrodes dopped with CuO contents show waves in the positive scanning of the current density because of the redox processes of the copper species. The XPS data of Pb 4f show clear evidences for valence fluctuations of lead ions in recycled and copper-doped samples.